Public and private families - Cherlin, Andrew (New York: McGraw-Hill Higher Education, 2001)
Contents : The history on the family ,gender and families,social class and families,race,ethnicity and families,the family,the state and social policy,sexuality and love,paths to family formation,spouses and partners,work and families,domestic violence,divorce,remarriage,children and parents,the elderly and their families,social change and families.
Keywords: Familia - Sociología Familiar